On homogeneous gold/palladium catalytic systems - Hashmi, A. Stephen K.; Lothschütz, Christian; Döpp, René; Ackermann, Martin; De Buck Becker, Janosc; Rudolph, Matthias; Scholz, Christian; Rominger, Frank (Advanced synthesis & catalysis, 2012)
Two substrates containing an aryl iodide and an allenoate ester were prepared and the gold-induced cycloisomerisation to vinylgold(I) species and their proto-deauration as well as the intramolecular palladium-catalysed cross-coupling reactions were investigated. Switching to catalytic amounts of gold and palladium and stoichiometric amounts of silver did indeed furnish the product of a cycloisomerisation/intramolecular cross-coupling. Control experiments revealed that silver cannot substitute for gold or palladium in these reactions, but a different palladium catalyst in a different oxidation state also afforded the cycloisomerisation/intramolecular cross-coupling products in only slightly reduced yields. By ICP analysis the palladium was shown to contain gold only at the sub-ppm level. This shows how carefully results obtained with such systems have to be interpreted. Then a series of allylic and benzylic o-alkynylbenzoates were investigated in gold- and palladium-catalysed reactions. For esters of benzyl alcohol and cinnamyl alcohol no palladium co-catalyst was needed for the conversion. All reagents were thoroughly checked for palladium traces by ICP analysis in order to thoroughly exclude a gold/palladium co-catalysis. Optimisation of the gold complex, counter ion and solvent showed that gold(I) isonitrile pre-catalysts and silver triflate as activator in dioxane are suitable to convert a number of substrates with aryl, alkyl and even cyclopropyl substituents. Crossover experiments proved an intermolecular allyl transfer.